Thermal properties and molecular interactions of alginate/gelatin hydrogel microparticles - Pilipenko, Nadezhda (2018)
Hydrogels are attractive materials for several engineering applications. They can be obtained, for example, from the combination of alginate and gelatin, and have been widely used in microencapsulation processes. In this work alginate/gelatin hydrogel microparticles were prepared based on the enzymatic crosslinking of gelatin (transglutaminase, TGase), and alginate gelation induced by calcium chloride (CaCl2). The evaluated conditions to study thermal properties, and molecular interactions between microparticle’s components where: gelatin amount (%wt, polymeric mixture-basis), TGase amounts (active units/ ggelatin) and contact time with CaCl2 (min). Four samples were obtained. For sample 1 the evaluated conditions were: gelatin amount 25 %wt; TGase amounts 10 U/g and contact time with CaCl2 81 min. For samples 2, 3 and 4: gelatin amount 75 %wt, 75 %wt and 75 %wt; TGase amounts 10 U/g, 30 U/g and 30 U/g and contact time with CaCl2 81 min, 21 min and 81 min, relatively. One formulation composed only by alginate (MAlginate) was also produced for comparison. The contact time with CaCl2 was 240 min. Fourier transform infrared spectroscopy (FTIR) and differential scanning calorimetry (DSC) confirmed that the studied variables influence both, thermal properties and the developed molecular interactions between the two polymers (alginate and gelatin) (fig.1). FTIR results show that a higher contact time with CaCl2 led to an increased level of alginate crosslinking. The use of TGase results in the increasing of the hydrogen bounded N-H groups. According to DSC results the use of TGase increases the thermal stability of crosslinked microparticles.